ANALISIS PENENTUAN PORTOFOLIO OPTIMAL DENGAN MODEL MARKOWITZ PADA ESG (ENVIRONMENTAL, SOCIAL, AND GOVERNANCE) STAR LISTED COMPANIES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fani, Rezki Fani; Nisa’ Faiza Saniya (Program Studi Manajemen Keuangan Syariah IAIN Parepare, 2024)
Stocks are one of the popular investment choices in Indonesia. When investing in stocks, investors are faced with two main choices, return and risk. Rational investor will always seek the optimal portfolio, which is a combination of company stocks that provide the highest return with low risk. One of the statistical models for determining the optimal portfolio is the Markowitz Model. This study aims to determine the optimal portfolio based on the Markowitz Model on ESG Star Listed Companies. This research was conducted qualitatively using secondary data using ESG (Environmental, Social, and Governance) Star Listed Companies stock data during the period of 2023 and Yahoo Finance. This study proves that the Markowitz Model is suitable for determining the optimal portfolio for ESG Star Listed Companies in Indonesia in 2023. The optimal portfolio generated by the Markowitz Model has a higher return than a randomly constructed portfolio with a lower risk level. The findings of this study provide the necessary information for investors who want to invest in ESG Star Listed Companies. Investors can use the Markowitz Model to design an optimal portfolio that matches their desired risk level.